2010
DOI: 10.1210/en.2009-0977
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aldosterone Synthase by Activator Transcription Factor/cAMP Response Element-Binding Protein Family Members

Abstract: Aldosterone synthesis is regulated by angiotensin II (Ang II) and K(+) acting in the adrenal zona glomerulosa, in part through the regulation of aldosterone synthase (CYP11B2). Here, we analyzed the role of cAMP response element (CRE)-binding proteins (CREBs) in the regulation of CYP11B2. Expression analysis of activator transcription factor (ATF)/CREB family members, namely the ATF1 and ATF2, the CREB, and the CRE modulator, in H295R cells and normal human adrenal tissue was performed using quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…7C). As previously shown by Nogueira & Rainey [8], both AngII and K + significantly increased the levels of ATF2 recruitment to the promoter region of CYP11B2 (~3.2-and ~2.7-fold over vehicle control, respectively), confirming that the CYP11B2 CRE sequence analysis (Fig. 5B) and found that K + treatment failed to induce detectable protein expression of NGFIB, NURR1, and NOR1.…”
Section: The Orphan Nuclear Receptor Ngfib Family Members Do Not Incrsupporting
confidence: 86%
See 2 more Smart Citations
“…7C). As previously shown by Nogueira & Rainey [8], both AngII and K + significantly increased the levels of ATF2 recruitment to the promoter region of CYP11B2 (~3.2-and ~2.7-fold over vehicle control, respectively), confirming that the CYP11B2 CRE sequence analysis (Fig. 5B) and found that K + treatment failed to induce detectable protein expression of NGFIB, NURR1, and NOR1.…”
Section: The Orphan Nuclear Receptor Ngfib Family Members Do Not Incrsupporting
confidence: 86%
“…It has been well established that AngII and K + both activate transcription of CYP11B2 through a common cis-regulatory element [7]. The CYP11B2 promoter contains a Ca 2+ /cAMP-response element (CRE) to which the CREB/ATF family proteins bind in response to AngII and K + [8]. Thus, AngII and K + are thought to share, at least in part, the CREB/ ATF-mediated transcription pathway.…”
Section: Rna Extraction and Qrt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Because H295R is a very difficult cell line to transfect (41,42), electroporation was performed with the Nucleofector system (Amaxa Biosystems) for efficient introduction of siRNAs (43,44). We observed that electroporation of siRNA mixtures, each directed against NGFIB or NURR1, led to a specific knockdown of the target gene without any apparent off-target cross-reactions between the members of the NGFIB family (Fig.…”
Section: From H295r Cells After 3 H Of Incubation With Angii or Vehicmentioning
confidence: 97%
“…However, ATF2 serves as a positive transcription factor that increases CYP11B2 expression. 20 Activation of ATF2 requires phosphorylation. Silencing of KL increased phosphorylation of ATF2 ( Figure 7B), which also could contribute to upregulation of CYP11B2 expression (Figure 6, D-F).…”
Section: Discussionmentioning
confidence: 99%